An atlas of ferroptosis-induced secretomes - Yapici, F. Isil; Seidel, Eric; Dahlhaus, Alina; Weber, Josephine; Schmidt, Christina; de Britto Chaves Filho, Adriano; Yang, Ming; Nenchova, Maria; Güngör, Emre; Stroh, Jenny; Kotouza, Ioanna; Beck, Julia; et al. (Cell death and differentiation, 2025)
Cells undergoing regulated necrosis systemically communicate with the immune system via the release of protein and non-protein secretomes. Ferroptosis is a recently described iron-dependent type of regulated necrosis driven by massive lipid peroxidation. While membrane rupture occurs during ferroptosis, a comprehensive appraisal of ferroptotic secretomes and their potential biological activity has been lacking. Here, we apply a multi-omics approach to provide an atlas of ferroptosis-induced secretomes and reveal a novel function in macrophage priming. Proteins with assigned DAMP and innate immune system function, such as MIF, heat shock proteins (HSPs), and chaperones, were released from ferroptotic cells. Non-protein secretomes with assigned inflammatory function contained oxylipins as well as TCA- and methionine-cycle metabolites. Interestingly, incubation of bone marrow-derived macrophages (BMDMs) with ferroptotic supernatants induced transcriptional reprogramming consistent with priming. Indeed, exposure to ferroptotic supernatants enhanced LPS-induced cytokine production. These results define a catalog of ferroptosis-induced secretomes and identify a biological activity in macrophage priming with important implications for the fine-tuning of inflammatory processes.
Gesehen am 29.10.2025